The Role of Content Marketing and Online Communities in Enhancing Binance Brand Loyalty across Asia - Dewi Pratiwi Indriasari (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study examines the role of content marketing and online communities in enhancing Binance brand loyalty across Asia. As cryptocurrency exchanges operate in an environment characterized by rapid technological innovation, market volatility, and regulatory uncertainty, understanding the marketing factors that foster long-term customer loyalty has become increasingly important. This study employed a quantitative research approach using a cross-sectional survey design. Data were collected from Binance users across selected Asian countries and analyzed using Structural Equation Modeling (SEM) with AMOS to examine the relationships among the proposed constructs. The findings indicate that the structural model achieved an acceptable level of goodness-of-fit, providing empirical support for the proposed conceptual framework. The analysis further demonstrates that content marketing and online communities play important roles in explaining variations in Binance brand loyalty, highlighting the significance of valuable digital content and active community engagement in strengthening long-term customer relationships. These findings suggest that educational content, knowledge sharing, and interactive community participation contribute to building stronger emotional attachment and sustained loyalty toward cryptocurrency exchange platforms. The novelty of this study lies in integrating content marketing and online communities within the context of cryptocurrency exchanges, particularly Binance across Asia, thereby extending the digital marketing and relationship marketing literature into a high-risk financial technology environment. The study offers practical implications for cryptocurrency platforms in designing customer-centric marketing strategies that promote trust, engagement, and sustainable brand loyalty.